Pengaruh dana pihak ketiga, non performing financing, dan financing to deposit ratio terhadap pembiayaan perbankan syariah di Provinsi Jambi - Mister Candera; Amri Amir; Dearmi Artis (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
This study aims to analyze: (1) the influence of third party funds, non-performing financing, and financing to deposit ratio on Islamic Banking assets; (2) the influence of third party funds, non-performing financing, financing to deposit ratio and assets to finance Islamic Banking; (3) the influence of third party funds, non-performing financing, and financing to deposit ratio against financing through Islamic banking assets. The data used are monthly financial statements from Sharia Commercial Banks and Sharia Business Units in Jambi Province in the period 2012-2014. The analytical tool used is path analysis. The results showed that (1) simultaneously and partially, Islamic banking assets in Jambi Province were influenced by variables of third party funds, non-performing financing, and financing to deposit ratio; (2) simultaneously the variable financing of Islamic banking in Jambi Province is influenced by, non-performing financing, financing to deposit ratios and assets. Partially, non-performin financing does not have a significant effect, while the other three variables have a significant effect (3) the amount of Islamic banking financing is influenced by third party funds variable that is equal to 0.587 with a total of 0.806 and financing to deposit ratio through asset variables of 0.195 with total influence which is equal to 0.300.